Advancing the clinical implementation of Clostridial cancer therapies - Zygouropoulou, Maria (2019)
Although tumour hypoxia and necrosis are a nemesis to the efficacy of conventional cancer therapies, they can be exploited by anaerobic bacteria for the selective targeting of solid tumours. Clostridium sporogenes lends itself well to this purpose, being a non-pathogenic, spore-forming and proteolytic obligate anaerobe. Intravenously injected spores of this organism profusely infiltrate, selectively germinate and naturally thrive in the hypoxic and necrotic regions of tumours, whilst non-germinated spores are eliminated. Capitalising on its inherent tumor-targeting capabilities, C. sporogenes can be genetically engineered to enhance its oncolytic properties as well as to incorporate safety features, cooperatively accelerating its translation towards clinical applications.